The Calls to Faith in Surah As-Saff and its Guidance for Spreading the Message: An Analytical Study - Dr. Abdulqader Omar Al-Huwaig (Journal of Scientific and Human Dimensions, 2026)
This study aims to identify Surah As-Saff, analyze its calls to faith, and derive guidance and lessons for preaching from it. The study also answers the following questions: What are the names of Surah As-Saff? How many verses does it have? What is the reason for its revelation? What are its main themes? What are the calls to faith contained in it? What is the overall opinion of the scholars of interpretation in analyzing its calls? What are the most important guidance and preaching benefits derived from it? As for the division of the research, after the introduction, it has been made into a preface, three sections, and a conclusion. The preface includes defining the research terms and the noble Surah The first requirement is the call to prohibit actions from contradicting words. It included an analytical interpretation of this call and its guidance for spreading the faith. One of its most important results was that combining words with deeds is a fundamental principle of spreading the faith and one of the most important means of calling to God. The second requirement is the call to encourage the trade that saves. It included an analytical interpretation of this call and its guidance for spreading the faith. One of its results was that the conditions for victory and empowerment are faith in God and His Messenger and striving in His cause with one’s life and wealth. The third requirement is the call to support the religion of God Almighty. It included an analytical interpretation of this call and its guidance for spreading the faith One of its findings was that no matter what calamities, defeats, and disasters befall the nation today, and no matter how great the challenges and obstacles, it will return to its former glory if it takes the necessary steps. The conclusion summarized the most important findings. This study called for focusing on the guidance, advice, and directives of the Holy Quran in the field of da’wah (calling to Islam) and reform, and for activating its role as a book in various aspects of life.